Conformational Bias by a Removable Silyl Group: Construction of Bicyclo[n.3.1]alkenes by Ring Closing Metathesis. Issue 10 (12th December 2017) - Lin, Minggui; Cai, Pei‐Jun; Zeng, Zhixiong; Lin, Na; Shen, Yang; Tang, Bin; Li, Fan; Chen, Chen; Yu, Zhi‐Xiang; Zhang, Yandong
Abstract: Herein, we report a novel strategy based on a conformationally controlled RCM by a removable silyl group, which allows the facile synthesis of various bicyclo[ n .3.1]alkenes, especially a set of highly strained bicyclo[5.3.1]alkenes. Further derivatizations of the silyl group and the resultant double bond of bicyclo[5.3.1]undecene2 f enabled a concise synthesis of A‐B‐C ring skeleton of taxol. Density functional theory (DFT) calculations suggest that the introduction of a bulky silyl group at C‐5 position of the 1, 3‐dialkenylcyclohexanol substrates dramatically lowers the energy bias gap between diaxial conformers (to RCM) and diequatorial conformers (to cross metathesis), thereby favoring the expected RCM reaction to give the challenging bridged molecules. Abstract : Conformation decides : we report a novel strategy based on a conformationally controlled RCM by a removable silyl group, which allows the facile synthesis of various bicyclo[ n .3.1]alkenes, especially a set of highly strained bicyclo[5.3.1]alkenes. Further derivatizations of the silyl group and the resultant double bond enabled a concise synthesis of A‐B‐C ring skeleton of taxol.